Can someone help?

http://latex.artofproblemsolving.com/1/4/3/143f7adfe5dbde261026c5f2225c12460a5b25a3.png

x³ = 20x + 7y y³ = 7x + 20y (x + y)³ = x³ + 3x²y + 3xy² + y³ (x + y)³ = x³ + y³ + 3xy(x + y) (x + y)³ = 27(x + y) + 3xy(x + y) (x + y)² = 27 + 3xy x² + 2xy + y² = 27 + 3xy x² + y² = 27 + xy (x - y)³ = x³ - 3x²y + 3xy² - y³ (x - y)³ = x³ - y³ - 3xy(x - y) (x - y)³ = 13(x - y) - 3xy(x - y) (x - y)² = 13 - 3xy x² - 2xy + y² = 13 - 3xy x² + y² = 13 - xy x² + y² = x² + y² thus 13 - xy = 27 + xy 2xy = -14 xy = -7

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up